2006
DOI: 10.1128/jvi.80.2.835-844.2006
|View full text |Cite|
|
Sign up to set email alerts
|

Neutralization Escape Variants of Human Immunodeficiency Virus Type 1 Are Transmitted from Mother to Infant

Abstract: Maternal passive immunity typically plays a critical role in protecting infants from new infections; however, the specific contribution of neutralizing antibodies in limiting mother-to-child transmission of human immunodeficiency virus type 1 is unclear. By examining cloned envelope variants from 12 transmission pairs, we found that vertically transmitted variants were more resistant to neutralization by maternal plasma than were maternal viral variants near the time of transmission. The vertically transmitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
267
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 276 publications
(287 citation statements)
references
References 52 publications
18
267
1
1
Order By: Relevance
“…Neutralization assays were performed using TZM-bl cells as previously described 16 . Heat-inactivated plasma samples (56°C, 1hr) were tested using six 2-fold serial dilutions, starting at 1:100.…”
Section: Methodsmentioning
confidence: 99%
“…Neutralization assays were performed using TZM-bl cells as previously described 16 . Heat-inactivated plasma samples (56°C, 1hr) were tested using six 2-fold serial dilutions, starting at 1:100.…”
Section: Methodsmentioning
confidence: 99%
“…Particularly, analyses of the role of passively transferred antibodies should clearly separate cases of intrapartum transmission from in utero transmission: only in cases of intrapartum transmission can we be sure that exposure to the virus occurs in the presence of optimal levels of IgGs. Supporting a role of maternal NAbs in limiting MTCT, several recent molecular studies have shown that viruses transmitted are escape variants resistant to autologous maternal plasma (Dickover et al, 2006; Wu et al, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…Here, we have evaluated the immunogenicity of a SOSIP.664 trimer based on the BG505 clade A virus, which was isolated from a 6-week old infant that later developed a bNAb response within ~2 years of infection (7, 8). We have also tested, in less detail, a second SOSIP.664 trimer based on a clade B adult infection founder virus, B41 (30).…”
mentioning
confidence: 99%